Optimization of qRT-PCR Annealing Temperature of WRKY45 Gene for Detection of Resistance Genes Against Xanthomonas oryzae pv. oryzae on Black Rice Cempo Ireng - Triyaningsih, Triyaningsih; Nuringtyas, Tri Rini; Purwestri, Yekti Asih; Sebastian, Alfino (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2022)
Plant pathogens constrain the development of black rice farming. One of these pathogens is Xanthomonas oryzae pv. oryzae (Xoo), causing a bacterial leaf blight disease. The disease disrupts crop growth and reducing yields. Cempo ireng is a local pigmented rice cultivar from Yogyakarta, Indonesia, which is reported for its high resistance to Xoo. One of the rice resistance mechanisms to Xoo infection is a molecular defense employing plant resistance genes such as WRKY45. Comparing the expression of resistance-related genes of the resistant cultivar to the susceptible ones is needed to elucidate the resistance mechanism of the black rice to Xoo. For this purpose, the expression of WRKY45 gene at the level of mRNA can be performed using qRT-PCR. The success of qPCR analysis is greatly influenced by the accuracy of the annealing primer temperature of the corresponding gene. This study aimed to optimize the primer's annealing temperature for WRKY45 gene. The optimization was done by a temperature gradient PCR. Determination of the optimal annealing temperature was selected based on the profile of the amplification curve, melt curve, melt temperature and the Ct value obtained. The annealing temperature gradient used in this study was ranging from 52°C to 60°C. The results showed that the best annealing temperature for WRKY45 gene primers is 58.3°C based on the amplification curve, melt curve, melt peak and Ct value of 29.21.